GENERATION Z INVOLVEMENT IN HALAL ECOSYSTEM - Ishak, Dandi; Akmal, Fadil Aulyah; Halide, Nirwana (Institut Agama Islam Negeri Bone, 2024)
Generation Z's involvement in the halal ecosystem in Indonesia, which has the largest Muslim population in the world, with a population of 277.53 million, of which 86% are Muslim, Indonesia has great potential to become a global halal product center. Generation Z, which consists of around 75.49 million people or 28% of the total population, shows high awareness of the halal lifestyle, which is reflected in their consumption patterns which are more critical and selective towards halal products. Generation Z influences their preferences for halal products, including easy access to information through social media and attention to health, sustainability, and social justice. Their involvement in the halal ecosystem is not only as consumers, but also as agents of change that can encourage the growth of the halal industry in Indonesia. In order to improve halal education and awareness programs among Generation Z through seminars, workshops, and information campaigns on social media, as well as involving halal industry practitioners. Thus, it is hoped that Generation Z can contribute significantly to the development of the halal market in the future, in line with existing regulations, such as Law No. 33 of 2014 concerning Halal Product Assurance. The active involvement of Generation Z in the halal ecosystem in Indonesia shows great potential for the growth and development of a sustainable halal industry.